PELATIHAN FUN GAMES BERBASIS STEAM PADA PENDIDIK ANAK USIA DINI - Eka Cahya Maulidiyah; Mallevi Agustin Ningrum; Ruqoyyah Fitri; Ajeng Putri Pratiwi (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2023)
The characteristics of early childhood who like to play in various activities require games that are interesting, innovative, close and concrete for children. Based on these needs, the PKM Team provides a solution by providing game-making training according to the needs of students through STEAM-based Fun Games Making Training. This training was carried out for PAUD teachers in Benjeng-Gresik District with the aim of teachers being able to make interesting, innovative, close and concrete games for children and integrated in various STEAM fields (Science, Technology, Engineering, Art and Mathematics). This series of community service activities is carried out over a period of 8 months from April to November 2022. Implementation begins with the drafting of the PKM concept, submission of PKM proposals, evaluation desk, designing the needs of PKM implementation, implementation of PKM, data collection and analysis of activities, fulfillment of PKM outputs, progress reports, and final PKM reports. The costs proposed to fulfill this series of PKM activities come from Unesa 2022 PNBP funds with the Faculty of Education Policy PKM scheme. The PKM partner is IGTKI, Benjeng District, Gresik Regency. The implementation method is carried out offline by providing conceptual understanding and followed up with STEAM-based game practices. The activity continued with periodic guidance from the PKM team to participants with the target of participants being able to implement STEAM-based games in their respective institutions. The output of PKM is in the form of videos of activity implementation, scientific articles in scientific journals, articles in online mass media and an MoU with IGTKI Partners, Benjeng District, Gresik Regency. For participants, this activity is useful in providing interesting STEAM-based games made by teachers so that they can be implemented in their respective institutions.